The birds from Department of Loreto, Peru - Salinas, Letty (2021)
We present an updated list of bird species from Department of Loreto. The list is based on the review of specimens from scientific collections, historical records, publications, and field observations. We report 1040 species of birds in Loreto, 72 in some threat category, 72 migratory and 13 endemics to Peru. Percnostola arenarum, Pithys castaneus and Polioptila clementsi are endemics to Loreto. The families with the highest numbers of species are Tyrannidae, Thamnophilidae and Thraupidae. The list presented is highly reliable due to the support of about 81% of the species on specimens from scientific collections and only 1.5% from sighting reports by ornithologists. Bird species from Loreto represent about 55% of the total reported for Peru and in Passeriformes 52% of those estimated for the Amazonia. The distribution of reports shows that it is necessary to explore areas close to the region's borders with Colombia and Brazil, as well as the mountain ranges shared with Amazonas and San Martin. Based on the distribution of threatened and endemic avifauna, we propose to prioritize the study and protection of montane areas and white-sand forests.